Multifunctional YY1 in Liver Diseases - Zhang, Mengjie; Zhang, Yi; Yang, Shuang; Zhou, Jian; Gao, Weiwu; Yang, Xia; Yang, Di; Tian, Zhiqiang; Wu, Yuzhang; Ni, Bing (Seminars in Liver Disease, 2017)
The transcription factor Yin Yang 1 (YY1) is a multifunctional protein that can activate or repress gene expression, depending on the cellular context. While YY1 is ubiquitously expressed and highly conserved between species, its role varies among the diverse cell types and includes proliferation, differentiation, and apoptosis. Upregulated YY1 expression is found in pathogenic conditions, such as human hepatocellular carcinoma and hepatitis B virus infection, and its roles in the molecular pathogenic mechanisms in liver (i.e., fibrosis, carcinogenesis, viral-induced injury) are currently being elucidated. The most recent studies have revealed that YY1 is deeply involved in such dysregulated cellular metabolisms as glycometabolism, lipid metabolism, and bile acid metabolism, which are all involved in various diseases. In this review, we will summarize the current knowledge on YY1 in liver diseases, providing a focused discussion on the characterized and probable underlying mechanisms, as well as a reasoned evaluation of the potential for YY1-mediated pathology as drug targets in liver disease therapies.
Keywords: YY1; viral hepatitis; liver fibrosis; hepatocellular carcinoma; cancer; metabolism